The Transgression toward Cooperation Principles, Implicatures, and Social Criticisms of Angkringan TVRI Jogja Humor Discourse (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Communication is basically a liability of cooperative principles although there are some transgression toward the principles. The transgression occurs on Angkringan TVRI Jogja humor. The purpose of this research is to analyse the transgression of the principles and implicature as well as to explain the intention and the delivered social criticism realization. The data is collected using observing and interview method. Observation uses listening method and participant observation method and nothing technique. The interview used uses eliciting technique, face to face and transcribing techniques. The data is analysed using coding technique by having categorization of selected elements and advanced technique by correlating and comparing the differences. In the discourse of Angkringan TVRI Jogja humour discourse, there are some transgression toward four principles. The most transgressed principle is relevancy principle. From the transgression, then it is created implicature containing social criticism. The criticisms mostly found in the discourse are related to social criticism in the form of revealing. The delivery of the criticism done by using humour is seen to be more effective because it has low offensive level.